New Insights in the Optic Radiations Connectivity in the Human Brain - Arrigo, Alessandro; Calamuneri, Alessandro; Mormina, Enricomaria; Gaeta, Michele; Quartarone, Angelo; Marino, Silvia; Anastasi, Giuseppe Pio; Aragona, Pasquale (Investigative ophthalmology & visual science, 2016)
To study optic radiations connectivity by means of advanced magnetic resonance imaging (MRI) approaches, noninvasively, in vivo, in healthy human brains. Sixteen healthy subjects (nine males, age range, 25-40 years) were included in this study. Morphologic and diffusion data were acquired by means of a 3T MRI scanner. Using an advanced tractographic technique, based on probabilistic constrained spherical deconvolution algorithm, postprocessing analyses were performed. Statistical analysis was carried out using the 2-tailed Wilcoxon rank sum test. Outcome measure was the percentage distribution of optic radiations streamlines in different cortical visual areas (V1-V5). The latter were detected by means of Juelich probabilistic histologic atlas. Average connectivity analyses revealed that the optic radiations are mainly distributed in V1 (47.46% ± 5.5) and V2 (32.45% ± 3.98); furthermore, direct connections with V3 (7.81 ± 3.06), V4 (4.22% ± 1.82), and V5 (8.06% ± 2.65) were also detected. In the present study, the connectivity profile of optic radiations, obtained by means of algorithms not affected by the limitations of other tractographic techniques, such as diffusion tensor imaging, was shown in healthy human brains. Interestingly, direct connections with V4 were detected for the first time in humans; moreover, further support on the possible existence of V5 connections was provided. Our findings showed new connections between lateral geniculate nuclei and cortical visual areas, giving a further possible comprehension of the phenomena leading to the visual signals elaboration.